Rancang Bangun Sistem Kerja Master Silinder Boster Rem Honda Berpaduan Dengan Rem Cakram BMW - Langgeng Rifa'i Ansori; Bahtiar Wilantara; Hamid Nasrullah (Politeknik Piksi Ganesha Indonesia, 2021)
The purpose of this study was to improve the quality of learning through the design of learning media for the Honda brake booster master cylinder working system combined with BMW disc brakes at the Dharma Patria Polytechnic Kebumen. The research method used is descriptive and documentation method. This research was conducted at the automotive lab of the Dharma Patria Polytechnic. The last test was carried out by students of the automotive mechanical engineering study program at the Dharma Patria Polytechnic. The results of the study show: 1) The learning media of the brake system works according to its function when the brake pedal is pressed 2) The assessment of the results of the questionnaire for learning media has a very effective comparison of 75%; quite effective 25%; less effective 60%; 3) the learning media for the braking system received a score from 2 media experts and was categorized as very suitable for use at the Dharma Patria Polytechnic.